Pengaruh Risiko Kerja Dan Upah Minimum Terhadap Produktivitas Kerja - Malakiyyah, Siti Nurhalifah; Tazliqoh, Agustifa Zea (Jurnal Ilmiah Wahana Pendidikan, 2025)
In the competitive business world, work productivity is an important factor for company success. This research examines how work risks and minimum wages affect work productivity. Using multiple linear regression analysis, this research collected data from 80 employees at Company "X" to understand the influence of work risks and minimum wages on work productivity. Based on the results of data analysis using multiple linear regression, it shows that both work risk and minimum wage have a positive influence on work productivity. This indicates that the greater the work risk and the minimum wage, the greater the work productivity of employees at Company "X". These findings emphasize the importance of effective risk management and fair wage policies to increase employee productivity